Patent Product Innovation Re-Design Based on Function Analysis - Cheng, Siyuan; Mi, Jingjing; Zhao, Rongli; Yang, Xuerong (Recent Patents on Mechanical Engineering, 2016)
Background: Function is the essential requirement of the user to the product and functional innovation is to optimize, update and restructure the function of the product. Objective: In this paper, the first objective is to accomplish function innovation re-design of patent product based on function analysis methods. Method: This method includes the following steps: function definition, re-design problem identification, problem solving and solution evaluation. Firstly, the total function is identified to build the function model based on patent claim of target patent. Then, judging whether there is a problem with the model and choosing the appropriate method of solving the problem. The method consists of two techniques: (a) using the method of patent around strategies based on TRIZ problemsolving tools to solve the innovation re-design problem; (b) applying the function tree structure and function change to solve function element, and to realize the patent product innovation re-design. Results: Finally, refining and optimizing the design concept to develop a new product. Results demonstrated that the method of patent innovation re-design based on function analysis is more accurate. Conclusion: Recent patent product study on the Red Wine Packaging is investigated to illustrate the method.
Keywords: function element